Sturm–Liouville problem with two point nonlocal second type boundary condition - Pečiulytė, Sigita; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2005)
The Sturm–Liouville problemwith one classical boundary condition and other two point second type nonlocalboundary conditions is considered in this paper. Three cases of nonlocal conditions are investigated.There is analysed how spectrum of this problem depends on boundary condition parameters. Qualitativebehavior of all eigenvalues subject to nonlocal second type boundary condition parameters is described.
Keywords: nonlocal boundary conditions; Sturm-Liouville problem